Materiały z cmentarzyska kultury pomorskiej z Orońska, woj. Radom, ze zbiorów Muzeum Okręgowego w Lublinie - Czopek, Sylwester (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
During rescue investigations in the site of Pomeranian culture in Orońsko two cinerary urns completly preserved and two fragmentarily preserved were found. The chronological analysis enables to classify them in the early stage of Pomeranian culture dated back to HD2-LA (500-400 B.C.).